2016
DOI: 10.1097/mib.0000000000000588
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D in Infliximab-induced Remission in Adult Patients with Crohnʼs Disease

Abstract: Crohn's patients initiating infliximab with a low vitamin D level are more likely to achieve infliximab-induced clinical remission at week 14.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Santos-Antunes et al demonstrated that extreme vitamin D deficiency (<20 ng/ml) was associated with serum antinuclear antibody (ANA) positivity, anti-TNF failure, and adverse events (OR = 20.11, 95% CI: 2.10-192.39) (69). However, Reich et al found that CD patients with a low serum vitamin D level had a higher clinical remission rate at 14 weeks than patients with normal vitamin D levels (80% vs. 23%, P = 0.007) (70).…”
Section: Vitamin Dmentioning
confidence: 98%
“…Santos-Antunes et al demonstrated that extreme vitamin D deficiency (<20 ng/ml) was associated with serum antinuclear antibody (ANA) positivity, anti-TNF failure, and adverse events (OR = 20.11, 95% CI: 2.10-192.39) (69). However, Reich et al found that CD patients with a low serum vitamin D level had a higher clinical remission rate at 14 weeks than patients with normal vitamin D levels (80% vs. 23%, P = 0.007) (70).…”
Section: Vitamin Dmentioning
confidence: 98%
“…Recent studies investigated a possible correlation between vitamin D levels and clinical response to infliximab therapy. Here, low baseline vitamin D concentration was associated with heightened probability of primary clinical remission at week 14 in CD patients ( 116 ). Another study in IBD patients, found a significant link between deficiency of vitamin D and the presence of ANA, which were found to be associated with failure to anti-TNF therapy and also reported as significant risk factors for anti-TNF induced adverse events associated with anti-TNF therapy ( 72 ).…”
Section: Blood Markersmentioning
confidence: 98%
“…From a clinical point of view, the administration of tumor necrosis factor (TNF)‐alpha inhibitor is associated with higher vitamin D levels in IBD . On the other hand, in CD patients where infliximab was initiated, lower vitamin D levels were associated with a higher rate of clinical remission at week 14 …”
Section: Introductionmentioning
confidence: 99%